Evaluation of microcrystalline cellulose II (MCCII) as an alternative extrusion-spheronization aid (2012)
ABSTRACT: Microcrystalline cellulose II (MCCII) is a different allomorph of MCC that can be used as a filler and a disintegrant for direct compression. MCCII was studied as new pelletization aid with the aim to prepare pellets with a faster drug release than MCCI-based pellets. MCCII-based pellets showed an immediate diphenydramineHCl release profile comparable to that of Benadryl and a faster griseofulvin release than MCCI-based pellets. MCCII offers potential to use as an alternative pelletization aid.